Implementation of Decentralized Systems in Electronic Election Applications - Prayogo, Ario; Sutanto, Imam (Jurnal Ilmu Kepolisian, 2025)
The e-voting system represents a digital innovation designed to enhance efficiency, transparency, and security in the election process. This research discusses the development of a blockchain-based e-voting system built on the Ethereum testnet (Sepolia), integrated with CodeIgniter 4, MySQL, and Tailwind CSS frameworks. The system was developed using the Prototyping method, enabling iterative improvement based on user feedback. The evaluation results indicate that each vote is successfully recorded on the blockchain through a smart contract, providing a verifiable transaction hash (tx_hash) as proof of authenticity. From a usability perspective, 73.7% of respondents stated that the system is easy to use, and 78.9% expressed willingness to adopt it. These findings demonstrate that the proposed blockchain-based e-voting system meets the criteria of usability, security, and user trust, showing strong potential for practical implementation at Esa Unggul University.